Psoriasis assessment tools in clinical trials. (11th February 2005) - Feldman, S R; Krueger, G G
Abstract : In clinical practice, broad global assessments of psoriasis disease activity and its effect on patients' quality of life are used to assess the severity of patients' disease and their response to treatment. In clinical trials, more objective, validated instruments are required. Several such instruments have been developed and continue to be developed to provide an assessment of the severity of the skin lesions. Because a lesion's impact on patients' lives varies widely among patients, there has been growing recognition of the need to measure the quality of life impact of the disease along with the severity of the lesions.